Nonprofit organizations: in what extent is internet being used to (re)connect stakeholders and organizations? An empirical study in Portuguese Foundations - Santos, M.; Laureano, Raul M. S.; Abreu, M. E. (ARNOVA 14, 2014)
Statistics reveal nonprofit organizations as the major employers and the major sources of employment growth in countries throughout the world. Although sources of financial support show different weights, it is a fact that donors and other stakeholders are becoming more interested in obtaining information about the efficiency and the effectiveness resources application. This research measures the extent in what NPO Foundations are disclosing on internet the information pointed out by literature as legally mandatory and as relevant for the stakeholders. Based on data collection from 86 IPSS Portuguese Foundations’ website, a bivariate analysis was undertaken and the main relevant statistics were presented. This paper brings an important overview about transparency status and communication between NPO and its stakeholders. The relevant observations of this study allowed us on identifying, firstly, the deficit on application of the legislation and, secondly, the low level of practices performed by IPSS Foundations in order to disclose relevant information for the stakeholders like: strategy, communication tools and other financial and non-financial information.